1997
DOI: 10.1055/s-2006-957707
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Essential Oil ofZataria multiflora

Abstract: The composition of the essential oil of Zataria multiflora Boiss. was studied by gas liquid chromatography (GLC), column chromatography (CC), NMR, and GLC/MS. The main constituents of the dry plant were thymol, carvacrol, while the main constituents of the fresh plant were thymol, carvacrol, p-cymene, linalool and gamma-terpinene. The structures of the major components were confirmed by IR and 1H-NMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 1 publication
5
54
2
Order By: Relevance
“…The results indicated that Zataria multiflora have a significant anti-fungal effect, which can be attributed to composers such as carvacrol and thymol (14,15). The antifungal activities in the present search have been reported before by other researchers (16)(17)(18).…”
Section: Discussionsupporting
confidence: 77%
“…The results indicated that Zataria multiflora have a significant anti-fungal effect, which can be attributed to composers such as carvacrol and thymol (14,15). The antifungal activities in the present search have been reported before by other researchers (16)(17)(18).…”
Section: Discussionsupporting
confidence: 77%
“…One aspect of such problem is the incidence of multidrug resistant bacteria like MRSA in hospitals. For resolving this problem, many investigators noticed the effect of herbal extracts instead of antibiotics (4,5). Based on the previous studies, the Avishen-e-Shirazi extract can inhibit the growth of enterohemorrhagic Escherichia coli (11), Salmonella sp and Shigella sp (12), S. aureus (13), Klebsiella (14), Enterococcus (15), Pseudomonas aeruginosa (16), and Acinetobacter baumannii, Alcaligenes, Chryseobacterium meningosepticum in the NFB (Non Fermentative Gram Negative Bacteria ) group.(13).…”
Section: Discussionmentioning
confidence: 99%
“…Z. multiflora is a member of the Lamiacea family and the most effective compounds in this medication are Thymol and Caracrol which have antibacterial effects (4). This plant grows in the south of Iran, Pakistan, India, and Afghanistan.…”
Section: Introductionmentioning
confidence: 99%
“…The compounds present in Z. multiflora boiss have antioxidant properties and are able to inhibit linoleic oxidation [10,11]. Z. multiflora essential oil has also been used for antimicrobial purposes in food [12,13].…”
Section: In Each Column Numbers That Have Similar Letters the Differementioning
confidence: 99%